Minimal clinically important difference for change in comfortable gait speed of adults with pathology: a systematic review. Issue 4 (5th May 2014) - Bohannon, Richard W.; Glenney, Susan S.
Abstract Rationale, aims and objectives Walking speed is an important performance variable, but information on the minimal clinically important difference (MCID) for the measure has not been consolidated. In this review, we aimed to summarize information on the MCID for change in comfortable gait speed measurements for patients with pathology. Methods Relevant literature was identified by searches of four databases (PubMed, Web of Knowledge, CINAHL and Scopus), hand searches and consultation with an expert. Inclusion required that articles reported a MCID for comfortable gait speed measurements. Articles were excluded if the MCID was not determined using receiver operating characteristic (ROC) curve analysis. Articles were abstracted for information on participants, interventions, gait speed documentation and the determination of MCID. Quality was assessed using a hybrid 9‐item (0–18 point) instrument. Results Seven articles were selected based on inclusion and exclusion criteria. The populations studied included stroke (n = 3), hip fracture (n = 2), multiple sclerosis (n = 1) and mixed (n = 1). Using 13 different anchors the studies reported MCIDs of 0.08–0.26 m s−1. All but three of these MCIDs were between 0.10 and 0.20 m s−1. All MCIDs for which the area under the ROC curve exceeded 0.70 were between 0.10 and 0.17 m s−1. Conclusions Changes in gait speed of 0.10 to 0.20 m s−1 may be important across multiple patient groups.